Training on the Use of Buku Warung to Improve the Capability of MSMEs RW 01 Pangaur Village, Bogor Regency - Mufti, Mufti; Nurwati, Nurwati; Santoso, Yudi; Indra, Indra (Edumedia Solution, 2025)
MSMEs play an important role in the country's economy, but unfortunately the capabilities of the perpetrators are not sufficient. For example, in terms of technology utilisation in the form of applications. Applications that facilitate business services are very important for the progress of MSMEs. One example is the Buku Warung application that can be downloaded through Playstore. In this application, there are features that allow users to record income and expenses for MSMEs such as grocery stores. With the Buku Warung application, MSME players can make digital records of income and expenses. In addition, this application is also able to compile and display financial reports in accordance with accounting standards for businesses conducted digitally. Through training in using the Buku Warung application, it is hoped that the abilities and skills of MSME players can increase for the development of their businesses in the future.